Colorless copper-zinc composite antibacterial phosphate glass and preparation method thereof
By optimizing the glass formula and preparation process, colorless copper-zinc composite antibacterial phosphate glass without the need for reducing agents, solving the problems of expensive, easy coloring and containing toxic and harmful elements of antibacterial glass, achieving colorless transparency, strong antibacterial properties and low cost effects.
Patent Information
- Application Number
- CN202311768607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-12-19
AI Technical Summary
Existing antibacterial glasses have the problem of expensive prices. Copper-containing antibacterial glasses are easy to color and contain toxic and harmful elements, which limits its application.
By optimizing the formula and preparation process of the glass, a colorless copper-zinc composite antibacterial phosphate glass is prepared without the need for additional reducing agent, which consists of P2O5, Cu2O, and ZnO. By controlling the raw material combination and preparation process, the glass mainly contains copper-ion Cu+, so it is colorless and transparent.
It realizes colorless and transparent antibacterial glass, has strong antibacterial properties, is widely used in different antibacterial fields, and reduces production costs and toxicity.
Smart Images

Figure HDA0004620470200000011 
Figure HDA0004620470200000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to a colorless copper-zinc composite antibacterial phosphate glass and a preparation method thereof. Background Art
[0002] Antibacterial glass mainly achieves its antibacterial function by releasing metal ions with antibacterial ability (such as silver ions, copper ions, zinc ions, etc.). Antibacterial glass can be processed into various forms, such as powder, sheet or fiber, etc., and introduced into plastics, coatings or textiles as an additive to give the products excellent antibacterial properties. Among the many antibacterial ions, silver ions have strong antibacterial activity, so the application of silver-containing antibacterial glass occupies a major position, but silver ions are highly toxic and expensive, resulting in low economic effects of related products. Copper and zinc not only have excellent antibacterial properties, but also the raw materials are widely distributed and inexpensive, which can greatly reduce the production cost of related products. However, copper is usually present in glass in the form of divalent (Cu 2+ ), which causes the glass containing divalent copper to generally appear blue-green. If it is introduced into the substrate, the antibacterial product will change color, greatly limiting its application space.
[0003] Generally speaking, when there are no special impurity ions, the color of the glass depends on the valence of copper, and the valence of copper in the glass is controlled by many factors, such as the chemical composition of the glass, the melting process (temperature, time, oxygen partial pressure and other conditions) and the type and content of the reducing agent. 2+ It is blue-green if it mainly contains Cu + It is colorless, and if it mainly contains Cu 0 In addition, if the glass mainly contains Cu + Not only is it colorless, but it also exhibits stronger bactericidal activity (Zhang Xinrui. Research on the antibacterial properties and antibacterial mechanism of copper-containing stainless steel [D]. University of Science and Technology of China, 2021).
[0004] In the process of melting glass, although regulating the oxygen partial pressure or adding a reducing agent can regulate the valence state of copper to avoid the coloration of copper-containing glass, the production of high-quality copper-containing colorless glass is limited by factors such as the kiln structure and the melting process. Chinese patent CN1340035A discloses a colorless borosilicate glass and a product made of the glass, wherein the glass matrix is composed of the following oxides, including SiO2, B2O3, Al2O3, Li2O, Na2O, K2O, CaO+BaO+SrO, Cu2O, CdO, ZrO2, C, Br, Cl+Br and F. This scheme uses a reducing agent (such as SnO2, As2O3, Sb2O3 and mixtures thereof) to regulate the morphology of copper so that it is mainly in the form of Cu +However, this glass belongs to borosilicate glass, which has lower antibacterial properties than phosphate glass, and the composition of the glass and the raw material reducing agent contain heavy metal elements, which is not conducive to its application in various antibacterial fields. Summary of the invention
[0005] The main purpose of the present invention is to solve a series of problems existing in the prior art, such as the high price of Ag-containing antibacterial glass, the easy coloration of Cu-containing antibacterial glass, and the presence of toxic and harmful elements in the antibacterial glass. By optimizing the formula and preparation process of the glass, a copper-containing phosphate glass is prepared without the need for an external reducing agent. The glass not only has a strong antibacterial effect but is also colorless and can be more widely used in different antibacterial fields. To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A colorless copper-zinc composite antibacterial phosphate glass comprises P2O5, Cu2O and ZnO.
[0007] Furthermore, the composition of the glass also includes at least one of BaO, CaO, SiO2, Al2O3, and B2O3. Among them, P2O5 constitutes the basic skeleton of the glass network; Cu2O dissolves in the glass network and provides the glass with super strong antibacterial properties as an antibacterial component; ZnO participates in the formation of the glass network or modifies the glass network skeleton on the one hand, and on the other hand, it also acts as an antibacterial component to further enhance the antibacterial properties of the glass; the addition of alkaline earth metal oxides BaO and CaO can reduce the viscosity of the glass liquid, making it easier to melt; SiO2, Al2O3 and B2O3, as glass formers, increase the connectivity of the glass network, enhance the chemical stability of the glass, and are beneficial to the long-term antibacterial properties of the antibacterial glass.
[0008] Further, the glass includes the following components in percentage by mass: 52%-65% P2O5, 30%-38% ZnO, 0%-15% BaO, 0%-10% CaO, 0%-6% SiO2, 0%-5% Al2O3, 0%-5% B2O3, 0.1%-2.0% Cu2O, totaling 100%.
[0009] Furthermore, the mass percentage content of each component in the glass is: 56%-64% P2O5, 32%-36% ZnO, 0%-10% BaO, 0%-5% CaO, 0%-2% SiO2, 0%-2% Al2O3, 0%-2% B2O3, 0.1%-1.5% Cu2O, totaling 100%.
[0010] Furthermore, the sum of the mass percentages of BaO, CaO, SiO2, Al2O3 and B2O3 in the glass does not exceed 10%. If the contents of these five components are too high, the glass may be colored.
[0011] Furthermore, the antibacterial targets include Escherichia coli.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned colorless copper-zinc composite antibacterial phosphate glass, comprising the following steps: preparing raw materials according to the composition of the glass and heating and melting them, and then cooling them.
[0013] Furthermore, the equipment used for melting the raw materials is an induction furnace, the melting temperature is 900-1100°C, preferably 950-1000°C, and the cooling rate is 10-100°C / s.
[0014] Furthermore, P2O5 in the glass composition is introduced in the form of NH4H2PO4, ZnO is introduced in the form of Zn3P2O8 or ZnO, Cu2O is introduced in the form of at least one of cuprous oxide, cupric oxide, and cupric carbonate, BaO and CaO are introduced in the form of their carbonates or oxides, SiO2 is introduced in the form of SiO2, Al2O3 is introduced in the form of Al2O3 or Al(OH)3, and B2O3 is introduced in the form of H3BO3 or B2O3.
[0015] The present invention selects NH4H2PO4 as the P2O5 raw material, which decomposes and releases a large amount of NH3 during the glass melting process, providing a weak reducing atmosphere for glass melting, promoting the Cu 2+ Reduction to Cu + , while preventing Cu in the raw materials + Oxidized to Cu 2+ ions, so that the Cu ions in the final glass product are mainly Cu + The prepared glass product exists in a colorless and antibacterial form.
[0016] Compared with the existing similar technologies or products, the advantages of the present invention are mainly reflected in the following aspects: (1) the raw materials are cheap, easy to obtain and non-toxic and harmless, and the colorless copper-zinc composite antibacterial phosphate glass prepared therefrom is widely used; (2) by controlling the raw material combination and the preparation process, the glass product mainly contains cuprous ions Cu + , so it is colorless and transparent and has strong antibacterial properties, and is easy to process into various forms and compound with substrates, and the compounding will not affect the color and use of the substrate; (3) The preparation process of the present invention is simple and easy to implement, without the need for external reducing agents, etc., which reduces the production cost and toxicity of the antibacterial material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The actual pictures and visible light absorption spectra of the colorless antibacterial glass prepared in Example 1 and Comparative Example 1 of the present invention;
[0018] Figure 2 This is a diagram showing the antibacterial ring test effect of the colorless antibacterial glass powder prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0019] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.
[0020] Example 1
[0021] A colorless copper-zinc composite antibacterial phosphate glass comprises the following components in terms of mass percentage: 62.5% P2O5, 36.1% ZnO, and 1.4% Cu2O.
[0022] The preparation method of the glass is as follows: prepare raw materials such as NH4H2PO4, Zn3P2O8 and CuO according to the designed ratio, add the weighed raw materials into an induction furnace and heat them to about 1000°C to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a speed of about 10°C / s, and finally form a colorless copper-zinc composite phosphate glass product. It is found by naked eye observation that the glass product prepared in this embodiment is indeed colorless and transparent (such as Figure 1 shown).
[0023] The glass sample was sampled and tested for visible light absorption. The results are as follows: Figure 1 As shown in the figure, it can be seen that the glass sample is colorless and its visible light absorption spectrum has no absorption in the visible light range (370-760nm).
[0024] The antibacterial performance of the prepared glass sample was tested by referring to the inhibition zone method of GB / T39101-2020 polypeptide antibacterial property determination, wherein the antibacterial ring width is 9 mm. The test results show that the colorless copper-zinc composite phosphate glass prepared in this embodiment has a good antibacterial effect on Escherichia coli.
[0025] Example 2
[0026] A colorless copper-zinc composite antibacterial phosphate glass comprises the following components in terms of mass percentage: 59.4% P2O5, 34.2% ZnO, 5% CaO and 1.4% Cu2O.
[0027] The preparation method of the glass is as follows: prepare raw materials such as NH4H2PO4, ZnO, CaCO3 and CuO according to the designed ratio, add the weighed raw materials into an induction furnace and heat them to about 950°C to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a speed of about 40°C / s, and finally form a colorless copper-zinc composite phosphate glass product. The glass is indeed colorless and transparent when observed with the naked eye.
[0028] The glass sample was sampled and tested for visible light absorption. The results showed that the visible light absorption spectrum of the glass sample had no absorption in the visible light range (370-760nm).
[0029] The antibacterial performance of the prepared glass sample was tested by referring to the inhibition zone method of GB / T39101-2020 polypeptide antibacterial property determination, wherein the antibacterial ring width is 6 mm. The test results show that the colorless copper-zinc composite phosphate glass prepared in this embodiment has a good antibacterial effect on Escherichia coli.
[0030] Example 3
[0031] A colorless copper-zinc composite antibacterial phosphate glass comprises the following components in terms of mass percentage: 56.4% P2O5, 32.3% ZnO, 10% BaO and 1.3% Cu2O.
[0032] The preparation method of the glass is as follows: prepare raw materials such as NH4H2PO4, ZnO, BaCO3 and Cu2O according to the designed ratio, add the weighed raw materials into an induction furnace and heat them to about 1000℃ to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a speed of about 60℃ / s, and finally form a colorless copper-zinc composite phosphate glass product. The glass product is indeed colorless and transparent when observed with the naked eye.
[0033] The glass sample was sampled and tested for visible light absorption, and the results showed that the visible light absorption spectrum of the glass sample had no absorption in the visible light range (370-760nm).
[0034] The antibacterial performance of the prepared glass sample was tested by referring to the inhibition zone method of GB / T39101-2020 polypeptide antibacterial property determination, wherein the antibacterial ring width is 5 mm. The test results show that the colorless copper-zinc composite phosphate glass prepared in this embodiment has a good antibacterial effect on Escherichia coli.
[0035] Example 4
[0036] A colorless copper-zinc composite antibacterial phosphate glass comprises the following components in terms of mass percentage: 56.5% P2O5, 32.3% ZnO, 2.9% BaO, 1.9% SiO2, 1.8% Al2O3, 1.8% B2O3, 1.5% CaO and 1.3% Cu2O.
[0037] The preparation method of the glass is as follows: prepare raw materials such as NH4H2PO4, Zn3P2O8, BaCO3, SiO2, Al2O3, H3BO3, CaCO3 and CuO according to the designed ratio, add the weighed raw materials into an induction furnace and heat them to about 950°C to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a speed of about 80°C / s, and finally form a colorless copper-zinc composite phosphate glass product. The glass product is indeed colorless and transparent when observed with the naked eye.
[0038] The glass sample was sampled and tested for visible light absorption. The results showed that the visible light absorption spectrum of the glass sample had no absorption in the visible light range (370-760nm).
[0039] The antibacterial performance of the prepared glass samples was tested according to the inhibition zone method of GB / T39101-2020 polypeptide antibacterial property determination, where the antibacterial ring width is 3mm. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the colorless copper-zinc composite phosphate glass prepared in this embodiment has a good antibacterial effect on Escherichia coli.
[0040] Example 5
[0041] A colorless copper-zinc composite antibacterial phosphate glass comprises the following components in terms of mass percentage: 64.5% P2O5, 35.4% ZnO, and 0.1% Cu2O.
[0042] The preparation method of the glass is as follows: prepare raw materials such as NH4H2PO4, ZnO and CuO according to the designed ratio, add the weighed raw materials into an induction furnace and heat them to about 950°C to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a speed of about 80°C / s, and finally form a colorless copper-zinc composite phosphate glass product. The glass product is indeed colorless and transparent when observed with the naked eye.
[0043] The glass sample was sampled and tested for visible light absorption, and the results showed that the visible light absorption spectrum of the glass sample had no absorption in the visible light range (370-760nm).
[0044] The antibacterial performance of the prepared glass sample was tested by referring to the inhibition zone method of GB / T39101-2020 polypeptide antibacterial property determination, wherein the antibacterial ring width is 2 mm. The test results show that the colorless copper-zinc composite phosphate glass prepared in this embodiment has a good antibacterial effect on Escherichia coli.
[0045] Example 6
[0046] A colorless copper-zinc composite antibacterial phosphate glass comprises the following components in terms of mass percentage: 52.0% P2O5, 30.0% ZnO, 9.8% BaO, 8.1% CaO and 0.1% Cu2O.
[0047] The preparation method of the glass is as follows: prepare raw materials such as NH4H2PO4, ZnO, BaCO3, CaCO3 and CuO according to the designed ratio, add the weighed raw materials into an induction furnace and heat them to about 950°C to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a speed of about 80°C / s, and finally form a colorless copper-zinc composite phosphate glass product. The glass product is indeed colorless and transparent when observed with the naked eye.
[0048] The glass sample was sampled and tested for visible light absorption, and the results showed that the visible light absorption spectrum of the glass sample had no absorption in the visible light range (370-760nm).
[0049] The antibacterial performance of the prepared glass sample was tested by referring to the inhibition zone method of GB / T39101-2020 polypeptide antibacterial property determination, where the antibacterial ring width is 1 mm. The test results show that the colorless copper-zinc composite phosphate glass prepared in this embodiment has a good antibacterial effect on Escherichia coli.
[0050] Comparative Example 1
[0051] A blue copper-zinc composite antibacterial phosphate glass comprises the following components by mass percentage: 62.5% P2O5, 36.0% ZnO, and 1.5% CuO.
[0052] The preparation method of the glass is as follows: prepare raw materials such as P2O5, Zn3P2O8 and CuO according to a designed ratio, add the weighed raw materials into an induction furnace and heat them to about 1000°C to completely melt them, cool the uniform glass liquid formed by high-temperature melting to room temperature at a rate of about 10°C / s, and finally form a blue copper-zinc composite phosphate glass product. It is found by naked eye observation that the glass product prepared in this comparative example is blue and transparent (such as Figure 1 shown).
[0053] The glass sample was sampled and tested for visible light absorption. The results are as follows: Figure 1 As shown in the figure, it can be seen that due to the blue color of the glass sample, its visible light absorption spectrum has obvious absorption in the visible light range (370-760nm).
Claims
1. A colorless copper-zinc composite antibacterial phosphate glass, characterized in that: The glass is composed of the following raw materials in percentage by mass: 52%-65% P2O5, 1.3%-2.0% Cu2O, 30%-38% ZnO, 0%-15% BaO, 0%-10% CaO, 0%-6% SiO2, 0%-5% Al2O3, and 0%-5% B2O3, wherein the sum of the mass percentages of BaO, CaO, SiO2, Al2O3, and B2O3 does not exceed 10%. The antibacterial target of the glass includes Escherichia coli. The preparation method is as follows: prepare the raw materials according to the composition of the glass, mix the raw materials evenly, and heat them to 900-11 00℃ is melted to obtain glass liquid, and the glass liquid is cooled and solidified at a cooling rate of 10-100℃ / s; wherein P2O5 is introduced in the form of NH4H2PO4 as a raw material, ZnO is introduced in the form of Zn3P2O8 or ZnO as a raw material, Cu2O is introduced in the form of at least one of cuprous oxide, cupric oxide and cupric carbonate as a raw material, BaO and CaO are introduced in the form of carbonate or oxide as a raw material, SiO2 is introduced in the form of SiO2 as a raw material, Al2O3 is introduced in the form of Al2O3 or Al(OH)3 as a raw material, and B2O3 is introduced in the form of H3BO3 or B2O3 as a raw material.
2. The colorless copper-zinc composite antibacterial phosphate glass according to claim 1, characterized in that: The glass has the following components in percentage by mass: 56%-64% P2O5, 32%-36% ZnO, 0%-10% BaO, 0%-5% CaO, 0%-2% SiO2, 0%-2% Al2O3, 0%-2% B2O3, and 1.3%-1.5% Cu2O.
3. The colorless copper-zinc composite antibacterial phosphate glass according to claim 1, characterized in that: The equipment used to melt the glass raw materials is an induction furnace.
4. The colorless copper-zinc composite antibacterial phosphate glass according to claim 1, characterized in that: The melting temperature is 950-1000℃.
Citation Information
Patent Citations
Colourless inorganic glasses with a sharp optical absorption cut off between 370 and 425 nm, products from said glasses
CN1340035A